Respostas

2014-04-10T17:12:08-03:00
x.(x+4)=32
x²+4x=32 
x²+4x-32 = 0 

Agora você resolve pela formula de baskara que é : -b +- 
√b²-4.a.c 
a = 1                                                                         2.a
b = 4
c=  -32
                                                       
x²+4x-32 = 0 

x = - (+4) +- √+4²-4.1.-32  
               2.1 
x= -4 +- √16 +128 
                2
x = -4 +- √144 
           2 
x = -4 +-  12 
          2 
x¹ = -4 + 12 =  = 4
          2          2

x²= -4 -12  = -16  = -8 
         2           2  
1 5 1